PENGARUH BEBAN KERJA DAN STRES KERJA TERHADAP KINERJA PEGAWAI DENGAN WORK-LIFE BALANCE SEBAGAI PEMODERASI PADA KPP MADYA BANDAR LAMPUNG - Yolanda Permata Yanra; Ni Putu Widhia Rahayu (PT. Saha Kreasi Indonesia, 2026)
Employee performance plays a crucial role in supporting organizational effectiveness, particularly in public institutions that face high service demands and revenue targets. Excessive workload and work-related stress may reduce employee performance when they are not balanced by supportive working conditions. This study aims to examine the effects of workload and work stress on employee performance and to investigate the moderating role of Work-Life Balance among employees of KPP Madya Bandar Lampung. A quantitative research approach was employed using a survey method involving 112 employees selected through a census technique. The data were analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The findings indicate that workload and work stress have a significant negative effect on employee performance. Furthermore, Work-Life Balance significantly moderates these relationships by mitigating the negative effects of workload and work stress on employee performance. These results suggest that maintaining a balance between work responsibilities and personal life contributes to sustaining employee productivity under demanding work conditions. Therefore, organizations are encouraged to implement policies that effectively manage workload, reduce work stress, and strengthen Work-Life Balance to enhance sustainable employee performance.